Current and future treatment of amyloid diseases. (10th May 2016) - Ankarcrona, M.; Winblad, B.; Monteiro, C.; Fearns, C.; Powers, E. T.; Johansson, J.; Westermark, G. T.; Presto, J.; Ericzon, B.‐G.; Kelly, J. W.
Abstract: There are more than 30 human proteins whose aggregation appears to cause degenerative maladies referred to as amyloid diseases or amyloidoses. These disorders are named after the characteristic cross‐β‐sheet amyloid fibrils that accumulate systemically or are localized to specific organs. In most cases, current treatment is limited to symptomatic approaches and thus disease‐modifying therapies are needed. Alzheimer's disease is a neurodegenerative disorder with extracellular amyloid β‐peptide (Aβ) fibrils and intracellular tau neurofibrillary tangles as pathological hallmarks. Numerous clinical trials have been conducted with passive and active immunotherapy, and small molecules to inhibit Aβ formation and aggregation or to enhance Aβ clearance; so far such clinical trials have been unsuccessful. Novel strategies are therefore required and here we will discuss the possibility of utilizing the chaperone BRICHOS to prevent Aβ aggregation and toxicity. Type 2 diabetes mellitus is symptomatically treated with insulin. However, the underlying pathology is linked to the aggregation and progressive accumulation of islet amyloid polypeptide as fibrils and oligomers, which are cytotoxic. Several compounds have been shown to inhibit islet amyloid aggregation and cytotoxicity in vitro . Future animal studies and clinical trials have to be conducted to determine their efficacy in vivo . The transthyretin (TTR) amyloidoses are a group of systemic degenerative diseases compromising multiple organ systems, caused by TTR aggregation. Liver transplantation decreases the generation of misfolded TTR and improves the quality of life for a subgroup of this patient population. Compounds that stabilize the natively folded, nonamyloidogenic, tetrameric conformation of TTR have been developed and the drug tafamidis is available as a promising treatment. Abstract : Content List – Read more articles from the symposium: Amyloid ‐ a multifaceted player in human health and disease.